Efektvitas Kombinasi Getah Pelepah Pisang Ambon (Musa paradisiaca L.) dan Jarak Pagar (Jathropha curcas L.) untuk Menyembuhkan Luka pada Marmut (Cavia porcellus) - Amal Fadholah; Salma Auliya Fatimah; Salma Cristy Syahidahalla (University Of Darussalam Gontor, 2019)
Wounds are a condition of damage or loss of some body tissue. Wounds can be cured with various drugs but have side effects and long healing times, one of which is Oxytetracyclin 3%. Jatropha sap has tannin, saponin, curcain protease and banana midrib having saponin, lectin, anthraquinone, quinone, flavonoid, tannin compounds which can be used to accelerate the healing process, antibacterial, and stop bleeding. This study aims to determine the effectiveness of the combination of banana stem sap and jatropha curcas to heal wounds in guinea pigs. This study is an experimental type with a completely randomized design (CRD) design using 4 treatments and 2 replications. The treatment used was a combination of banana midrib and jatropha sap with a ratio of 4%: 4%, 8%: 8%, 16%: 16% and positive controls using Oxytetracyclin 3%. The sap of the banana midrib and the distance of the fence are made in the form of ointments. Data in the form of the number of days from the formation of wounds to guinea pigs until the wound heals. The results showed that the combination of jatropha resin and sap of Ambon banana stem can provide the best wound healing effect at a concentration of 16%: 16% with the fastest wound healing time in 6 days.